Antimicrobial activity of autoclaved and non autoclaved copaiba oil on Listeria monocytogenes - Pieri,Fábio Alessandro (2010)
The aim of this study was to evaluate the antimicrobial effect of different copaiba oil concentrations against the growth of Listeria monocytogenes, and analyze differences in inhibition of microorganisms with autoclaved and non autoclaved oil. This study provided an agar diffusion test with six isolates of bacteria and six different concentrations of autoclaved or non autoclaved copaiba oil and a negative control. The results showed sensitivity of five L. monocytogenes isolates related to the 10% autoclaved solution of copaiba oil. Four strains also showed sensitivity to the 5% autoclaved solution and one to 2.5% autoclaved solution. The 10% non autoclaved oil solution showed growth inhibition only for two strains. These results had pointed the 10% autoclaved solution of copaiba oil with higher inhibition as all other solutions and concentrations tested (P<0.05). For the other concentrations of both solutions, the 5 and 2.5% autoclaved and 10% non autoclaved solutions had presented statistically equal. All other concentrations of both copaiba solutions and the negative control did not presented any bacteria inhibition. In conclusion, the results of this study suggest that the autoclaved copaiba oil may be a potential new agent source for infection control or for food preservation, inhibiting the growth of food-borne bacteria such as L. monocytogenes.